Construction of Heroism in Post-Reformasi Indonesian Biopic Films - Zuhdan Aziz; Aries Budi Marwanto (Lembaga Bale Literasi, 2026)
This article examines how post-Reformasi Indonesian biopic films construct heroism through historical selection, narrative condensation, and cinematic dramatization. The study is significant because biopic films do not merely visualize national figures; they also mediate collective memory, organize public emotion, and reshape the cultural imagination of heroism. Using a qualitative method with narrative analysis and cultural studies perspectives, this article reads six Indonesian biopics: Gie, Soegija, Sang Kiai, Soekarno, Jenderal Soedirman, and Kartini. The analysis focuses on the position of the hero in the plot, selected historical events, causal relations between individual action and social structures, visual-symbolic evidence, and the ideological values naturalized by the resolution. The findings show that post-Reformasi biopics construct heroism through four interrelated patterns. First, they transform historical complexity into popular historiography through selection, emphasis, and condensation. Second, the three-act structure works as an affective and ideological device that guides spectators from recognition of injustice to moral resolution. Third, heroism shifts from a monumental cult of great individuals to more humanized, ambivalent, and contextual figures. Fourth, cinematic space, body, and national symbols function as narrative evidence that links personal struggle with collective meaning. The article concludes that Indonesian hero biopics are arenas of negotiation between history, ideology, collective memory, and popular aesthetics.